School Choice and Loss Aversion - Vincent Meisner; Jonas von Wangenheim (Center for Economic Studies and ifo Institute (CESifo), 2021)
Evidence suggests that participants in direct student-proposing deferred-acceptance mechanisms (DA) play dominated strategies. To explain the data, we introduce expectation-based loss aversion into a school-choice setting and characterize choice-acclimating personal equilibria in DA. We find that non-truthful preference submissions can be strictly optimal if and only if they are top-choice monotone. In equilibrium, DA may implement allocations with justified envy. Specifically, it discriminates against students who are more loss averse or less confident than their peers, and amplifies already existing discrimination. To level the playing field, we propose sequential mechanisms as alternatives that are robust to these biases.
Keywords: C78; D47; D78; D81; D82; D91; 330; market design; matching; school choice; reference-dependent preferences; loss aversion; deferred acceptance